Physics of Brain Cancer: Multiscale Alterations of Glioblastoma Cells under Extracellular Matrix Stiffening - Mohammad Khoonkari; Dong Liang; Marleen Kamperman; Frank A. E. Kruyt; Patrick van Rijn (MDPI AG, 2022)
The biology and physics underlying glioblastoma is not yet completely understood, resulting in the limited efficacy of current clinical therapy. Recent studies have indicated the importance of mechanical stress on the development and malignancy of cancer. Various types of mechanical stress activate adaptive tumor cell responses that include alterations in the extracellular matrix (ECM) which have an impact on tumor malignancy. In this review, we describe and discuss the current knowledge of the effects of ECM alterations and mechanical stress on GBM aggressiveness. Gradual changes in the brain ECM have been connected to the biological and physical alterations of GBM cells. For example, increased expression of several ECM components such as glycosaminoglycans (GAGs), hyaluronic acid (HA), proteoglycans and fibrous proteins result in stiffening of the brain ECM, which alters inter- and intracellular signaling activity. Several mechanosensing signaling pathways have been identified that orchestrate adaptive responses, such as Hippo/YAP, CD44, and actin skeleton signaling, which remodel the cytoskeleton and affect cellular properties such as cell-cell/ECM interactions, growth, and migration/invasion of GBM cells. In vitro, hydrogels are used as a model to mimic the stiffening of the brain ECM and reconstruct its mechanics, which we also discuss. Overall, we provide an overview of the tumor microenvironmental landscape of GBM with a focus on ECM stiffening and its associated adaptive cellular signaling pathways and their possible therapeutic exploitation.